Koneksi Matematis Siswa pada Tugas Matematis Berbasis Hasil Pertanian: Konteks, Konsep, dan Prosedur Matematis - Ai Tusi Fatimah (Jurnal Elemen, 2021)
The mathematical connection is a crucial ability possessed by vocational high school students in solving problems by their field of expertise. Agriculture is a field of expertise that requires a lot of mathematical connection skills to solve various problems. Increasing the ability of students' mathematical connections can be facilitated by the teacher by constructing mathematical tasks in the agricultural sector. This qualitative research using the case study method describes the construction of mathematical tasks based on agricultural products and the mathematical connection ability of students in solving the task. Mathematical task construction is carried out by integrating agricultural product contexts and mathematical concepts. The mathematical task was used in Grade X Agribusiness Expertise students of Agricultural Product Processing. Data retrieval of students' mathematical connection abilities was carried out through tests, observation results, answer sheets, and interviews that focused on connecting contexts with mathematical concepts, connections between mathematical concepts, and connections to mathematical procedures. The results of the student data analysis showed that the ability of mathematical connections was hampered by the ability of the connection between mathematical concepts. It is necessary to increase student's mathematical connections by constructing mathematical tasks with various mathematical concepts.